2012
DOI: 10.2169/internalmedicine.51.6789
|View full text |Cite
|
Sign up to set email alerts
|

Ring-enhanced Brainstem Lesion in a Patient with Neuro-Behcet's Disease

Abstract: A 56-year-old man with oral and genital ulcers and folliculitis presented with distally dominant moderate weakness and impaired sensation with painful paresthesia in the right upper extremity. He presented with spastic paresis of the left lower extremity with Babinski sign. Tendon reflex was absent in the right upper extremity. Cerebrospinal fluid analysis showed mild mononuclear pleocytosis. MRI showed a solitary ring-enhanced lesion in the right pontine base with a high-intensity signal on diffusion-weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Varying patterns were observed on MRI throughout the patient history: (a) hyper-intensity on T2WI at the globus pallidus, (b) ring-enhancing lesion with central hyper-intensity on DWI, and (c) multiple patchy hyper-intense areas on DWI, T2WI, FLAIR, and Gad-T1WI. The findings of (a) and (c) correspond to the presentation of A-P-NBD, whereas those of (b) may correspond to NBD, as some case reports described NBD causing ring-enhancing lesions [2629]. Nishino et al reported that GPA can cause cerebritis, but it is rare among the other neurological manifestations in GPA (approximately 4%) [30].…”
Section: Discussionmentioning
confidence: 97%
“…Varying patterns were observed on MRI throughout the patient history: (a) hyper-intensity on T2WI at the globus pallidus, (b) ring-enhancing lesion with central hyper-intensity on DWI, and (c) multiple patchy hyper-intense areas on DWI, T2WI, FLAIR, and Gad-T1WI. The findings of (a) and (c) correspond to the presentation of A-P-NBD, whereas those of (b) may correspond to NBD, as some case reports described NBD causing ring-enhancing lesions [2629]. Nishino et al reported that GPA can cause cerebritis, but it is rare among the other neurological manifestations in GPA (approximately 4%) [30].…”
Section: Discussionmentioning
confidence: 97%
“…, lower images). A few cases of ring‐enhanced lesions in patients with acute NBD have been reported . Because the magnetic resonance imaging findings for acute NBD and brain abscesses look similar, it is difficult to distinguish these two conditions.…”
mentioning
confidence: 99%
“…A few cases of ring-enhanced lesions in patients with acute NBD have been reported. 1,2 Because the magnetic resonance imaging findings for acute NBD and brain abscesses look similar, it is difficult to distinguish these two conditions. It should be noted that multiple ring enhancement lesions in the magnetic resonance imaging might occur in patients with acute NBD, and that steroid therapy should be started as soon as the brain abscess is distinguished.…”
mentioning
confidence: 99%